Figurative Languages in Rita Ora’s Selected Song Lyrics - Ni Made Verayanti Utami; Ni Nyoman Deni Ariyaningsih; Ni Made Rai Desvita Sastra Dewi (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
The chosen song lyrics of Rita Ora are the subject of the investigation. The song lyrics were analyzed using Knickerbocker and Renninger's (1963:367) theory to determine the types of figurative languages found in the song lyrics, Leech's (1981:9-19) theory of meaning to describe the meaning of each type of figurative language found, and Halliday's (1985:10) theory to analyze the context of the situation in Rita Ora's selected song lyrics. The data for this study was gathered using descriptive qualitative methods. This study looked at ten different types of figurative language in Rita Ora's song lyrics. The most frequent appearance was irony. Connotative meaning, affective meaning, conceptual meaning, collocative meaning, social meaning, reflected meaning, and thematic meaning were discovered. All song lyrics emphasize connotative meaning. Before delving into the meaning of the ten Rita Ora songs, it is necessary to first determine the context of the situation in the song. The data is then analyzed to determine the field, tenor, and mode. Field is used to analyze what happens in the song, tenor is used to determine who participates in the song, and mode is used to determine how the data is conveyed.